Implementation of Self-Regulated Learning Model In Learning English Writing - La Ode Nggawu; Hartati Muchtar; Khaerudin Khaerudin (STKIP Singkawang, 2018)
This Academic article discusses the implementation of self-regulated learning model in English Writing learning, especially on enriching writing skill. The discussion of this article uses many points of views of self-regulated model learners, such as Albert Bandura, Barry Zimmerman, Anananita Bramuci, Popa Daniela, and Ernesto Panadero. According to the authors' interpretation, the discussion shows several results. (1) English writing skills require serious effort and practice in formulating, developing and analyzing ideas, especially for second /foreign language learners. (2) The understanding of English language grammar and vocabulary is indispensable for second / foreign language learners. (3) The self-regulated learning model can increase the learning motivation because this model encourages students to acquire knowledge and skills on their own voluntarily; and (4) learners who have high self-regulated learning, will have good learning outcomes as well.